2018
DOI: 10.1089/mdr.2017.0165
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of NDM-1-ProducingKlebsiella pneumoniae, Associated with OmpK35 and OmpK36 Porin Loss in Tunisia

Abstract: This study describes an outbreak of NDM-1-producing K. pneumoniae strains, isolated from a Tunisian hospital, caused by two clones belonging to ST147 and ST307; and highlights the role of OMPs loss, in combination with β-lactamase expression, in conferring high carbapenem resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Loss of porins is one of the factors contributing to antimicrobial resistance and may favor the selection of additional mechanisms of resistance. OmpK35 and OmpK36 are especially related to resistance to ␤-lactams and quinolones (104).…”
Section: Porin Detectionmentioning
confidence: 99%
“…Loss of porins is one of the factors contributing to antimicrobial resistance and may favor the selection of additional mechanisms of resistance. OmpK35 and OmpK36 are especially related to resistance to ␤-lactams and quinolones (104).…”
Section: Porin Detectionmentioning
confidence: 99%
“…Both global and regional surveillance of drug resistance is fundamental for the implementation of adequate infection control measures and disease management [3]. For this reason, some research groups from Mexico have reported the drug resistance rates of some bacterial pathogens, including Enterobacter sp., Klebsiella pneumoniae , Acinetobacter baumannii , Pseudomonas aeruginosa , Staphylococcus aureus , and Enterococcus faecium [47]; with species producing extended-spectrum beta-lactamases (ESBLs) or carbapenemases receiving special consideration [813].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently prescribed carbapenems include ertapenem, imipenem, and meropenem. Unlike other b-lactam antibiotics, carbapenems have the broadest antibacterial spectrum (2).…”
mentioning
confidence: 99%
“…The use of carbapenems for MDR bacterial infections created a selection pressure within the clinical setting, resulting in the emergence of carbapenem resistance (2). Carbapenem resistance is primarily mediated by carbapenemase genes found on mobile genetic elements such as plasmids, integrons, insertion sequences, and transposons, allowing for easier horizontal transfer of genes across and within different bacterial species (9)(10)(11)(12).…”
mentioning
confidence: 99%